2019
DOI: 10.3390/biom9110653
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profile Alteration with Cadmium Selenide/Zinc Sulfide Quantum Dots in Saccharomyces cerevisiae

Abstract: Quantum Dots (QDs) are becoming more prevalent in products used in our daily lives, such as TVs and laptops, due to their unique and tunable optical properties. The possibility of using QDs as fluorescent probes in applications, such as medical imaging, has been a topic of interest for some time, but their potential toxicity and long-term effects on the environment are not well understood. In the present study, we investigated the effects of yellow CdSe/ZnS-QDs on Saccharomyces cerevisiae. We utilized growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 58 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…The only common enzyme to the 9 and 24 h exposure times was Ald4, the level of which initially increased at 9 h and decreased at 24 h. As reported earlier, ENMs treatment inhibits the glycolytic pathway and stimulate fermentation [ 56 ]. Horstmann et al, (2019) suggested that sugar transport genes and sugar-utilising enzyme genes are simultaneously affected by the presence of Cd-QDs [ 57 ]. The two isoforms of GAPDH (Tdh1, Tdh2) were found to be upregulated for both treatment times.…”
Section: Resultsmentioning
confidence: 99%
“…The only common enzyme to the 9 and 24 h exposure times was Ald4, the level of which initially increased at 9 h and decreased at 24 h. As reported earlier, ENMs treatment inhibits the glycolytic pathway and stimulate fermentation [ 56 ]. Horstmann et al, (2019) suggested that sugar transport genes and sugar-utilising enzyme genes are simultaneously affected by the presence of Cd-QDs [ 57 ]. The two isoforms of GAPDH (Tdh1, Tdh2) were found to be upregulated for both treatment times.…”
Section: Resultsmentioning
confidence: 99%
“…Through further studies, no noteworthy changes in superoxide were noticed, with or without CdSe/ZnS–QDs treatment. Overall, results through transcriptome analysis indicated the exposure of CdSe/ZnS–QDs within yeast remarkably affected genes associated in multiple cellular processes [ 143 ].…”
Section: Selenium In Physics Surfaces and Nanoscience With Regarmentioning
confidence: 99%
“…An assay to measure the reactive oxygen species (ROS) was performed over a three-day period as described before [14][15][16]. Initially, cells were cultured and counted.…”
Section: Reactive Oxygen Species Assaymentioning
confidence: 99%
“…The wells were mixed thoroughly by pipette and centrifuge, and the plate was put into QuantStudio 6 Pro instrument (Thermo Fisher Scientific, Waltham, MA, USA) for PCR amplification. Changes were detected in comparison to the housekeeping gene (CCT2) using the Pfaffl method [14,15,17]; the gene expression ratio of each target gene was calculated based on E (RT-qPCR efficiencies) and Cq value deviation from the control (CCT2 expression levels).…”
Section: Rt-qpcrmentioning
confidence: 99%